Impotenza e terapia farmacologica (Stato, Chiese e pluralismo confessionale, 2015)
Il contributo riproduce il testo della relazione svolta al XLVII Congresso Nazionale dell’Associazione Canonistica Italiana, dedicato al tema Matrimonio e processo: la sfida del progresso scientifico e tecnologico (Gaeta, 7-10 settembre 2015), i cui Atti saranno pubblicati dalla Libreria Editrice Vaticana.SOMMARIO: 1. Note preliminari – 2. Le nuove terapie farmacologiche dell’impotenza (cenni) – 3. L’humano modo dell’unione sessuale – 4. Perpetuità dell’impotenza, ordinarietà/straordinarietà e liceità/illiceità dei mezzi terapeutici – 5. Una questione bioetica: uso o abuso del farmaco. ABSTRACT: The paper concerns the new pharmacological therapies for impotence treatment and their effects on the copulative impotence as an impediment to marriage in canon law of Catholic Church. The most known medicament is viagra, first commercial name of active ingredient sildenafil, but subsequently other drugs have been discovered and experimented. These drugs can successfully treat many kinds of erectile dysfunction, once incurable, so as to be considered almost a “revolution” in the therapy of impotence. From the canon law point of view, the new pharmacological therapies, according to the author, are not opposed to the characteristic of “humano modo” required for conjugal act (can. 1061, § 1), and they can be considered as licit and ordinary means of therapy. In this way, they extend and safeguard the right to marriage (ius connubii), that is a human and Christian fundamental right.